2013
DOI: 10.3390/ma6051608
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Thermal Cycling Test of Microencapsulated Paraffin Wax/Polyaniline Made by Simple Preparation Method for Solar Thermal Energy Storage

Abstract: Microencapsulated paraffin wax/polyaniline was prepared using a simple in situ polymerization technique, and its performance characteristics were investigated. Weight losses of samples were determined by Thermal Gravimetry Analysis (TGA). The microencapsulated samples with 23% and 49% paraffin showed less decomposition after 330 °C than with higher percentage of paraffin. These samples were then subjected to a thermal cycling test. Thermal properties of microencapsulated paraffin wax were evaluated by Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 22 publications
(26 reference statements)
4
38
0
Order By: Relevance
“…Thermal cycling test device is operated in this study until 1000 cycles. The amount of those cycles are similar to the research of Silakhori M et al [22]. In Fig 4 shows the schematic of thermal cycling test.…”
Section: Thermal Cycling Testsupporting
confidence: 65%
See 1 more Smart Citation
“…Thermal cycling test device is operated in this study until 1000 cycles. The amount of those cycles are similar to the research of Silakhori M et al [22]. In Fig 4 shows the schematic of thermal cycling test.…”
Section: Thermal Cycling Testsupporting
confidence: 65%
“…Silakhori M et al utilized stainless steel heater which was sticked on a rectangular box that made of copper and filled by PCM sample to be heated. A heat pipe heat sink with fan was also sticked on that box to help the cooling process [22].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 2b~d, however, the fractured surfaces of the LDPE/PW composite films grew rougher with increasing PW content, producing micron-sized crystals [34,35]. The gray regions and round spots indicate the bulk of the LDPE matrix and PW, respectively, showing that there is an apparent phase separation between LDPE and PW.…”
Section: Morphological Structurementioning
confidence: 90%
“…The thermal cycling test revealed that the thermal reliability of these three PCMs were good after 500 and 1000 thermal cycles [14]. Silakhori et al studied the 1000 thermal cycles of the micro-encapsulated paraffin wax/polyaniline and reported that developed PCM was stable with respect to the thermal cycles [15].…”
Section: Introductionmentioning
confidence: 98%